南洋理工大学在籍华族学生婚姻观 = Chinese undergraduates' views on marriage : a case study of Nanyang Technological University - 吴起慧 Goh, Qi Hui (2009)
20 世纪 80 年代以来，新加坡明显地面临结婚及生育率下降的问题。这对国家、经济、社会都可能造成不良的影响。因为，婚姻的影响层面不只止于个人，而是会扩大至家庭、族群、国家等。迟婚或是不婚的现象，在大学毕业生身上尤为明显。作为社会的“小我”，任何行为都可能影响“大我”的发展。大学生在毕业后，步入社会工作，便会成为毕业生，两者之间有着紧密的联系。从前者身上能合理推测后者的婚姻行为。因此本论文将以南大生为考察对象，通过他们的婚姻观来研究一些婚姻的现象。虽然想法不能代表行为，但却能从中推断未来的行为模式。若想法与实际行为之间有差距，即表示有其他造成改变的因素。本文也将就这些因素进行论述。由于婚姻观是一个具延续性的研究课题，因此本文也将利用十年前的婚姻观调查与本文的调查做对比，以看出婚姻观的变化。除此之外，本文也将利用一些政府资料与本文的调查相比较，来看大学生的婚姻观以及毕业生的婚姻行为之异同。同时，也将以传统华人家庭及性别研究为切入点，试图审思两者对婚姻的影响。Since 1980s, Singapore has been persistently facing the problems of later marriages and delayed child-bearing. These trends could bring much detriment to the country; particularly to the economy and society. Marriage is not entirely an individual matter; as a member of the society, any action could go so far as to affect the progress of an entire nation. These trends of later marriages are rather pronounced amongst graduates. So taking undergraduates to be a close proxy of graduates; through examining undergraduates’ attitudes towards marriage, one can make logical deduction of graduates’ eventual marital decisions. In this thesis, NTU undergraduates’ marriage views would be used as an indicator of certain marriage trends. Although views do not necessarily represent actions, they are a reasonable gauge for future actions. In the case of divergence between views and actions, it can be safe to attribute this to other external causes (which this thesis would be attempting to answer as well). Owing to the nature of study, this thesis would be conducting a survey with current NTU undergraduates, and comparing the results with a marital perception study from 1998. This would help in the understanding of possible change in marriage views. Besides the aforementioned, this thesis would be using government statistics in comparison with the current survey, to look at the differences in marital views and actions. Traditional Chinese family and gender studies are also engaged as supporting concepts to scrutinize how much they shape current marital views and actions.